An Experimental Study on the Infiltration Potential of Stormwater Ponds in Zeekoe Catchment, Cape Town, South Africa - Mavundla, Kgomoangwato (Department of Civil Engineering, 2023)
In early 2018, the city of Cape Town, with a population of approximately 3.8 million, was at risk of running out of water from the six large reservoirs to the east of the city. This was due to the worst drought in almost a century, which occurred between 2015 2017, causing the city to be declared a disaster area. Although alternative water resources had been identified, they had not been developed. This has now become imperative as droughts are expected to recur in the future. This study investigated the prospect of using existing stormwater ponds in the Zeekoe catchment area as infiltration cells transferring detained stormwater into the underlying aquifer storage zone to enhance the available groundwater resource. The Zeekoe catchment is a 89 km2 area within the 630 km2 Cape Flats Aquifer (CFA). Based on hydrogeological data and aquifer parameter interpretation, it is considered to have good storage characteristics that can support groundwater development for water supply. Bouwer (2002) highlights how infiltration tests in the field can be useful for estimating desired volumetric recharge rates within a certain area. The hydraulic conductivity of the unsaturated layer is an essential non-linear function of soil-water content and has been generally recognised as the most important transport property to describe the ability of soil to permit water movement. A series of in-situ infiltration experiments were conducted at three representative stormwater ponds using a Double Ring Infiltrometer (DRI) to determine the rate of water recharge. Infiltration data was interpreted using both the Green-Ampt and Horton methods to determine the hydraulic conductivity and infiltration decay constants. A total of 18 core samples retrieved from the in-situ infiltration test locations were analysed in the laboratory to determine the ed hydraulic conductivity through constant-head permeability (CHP) tests. The physical and hydraulic soil parameters gathered from field and laboratory tests were used as inputs for a finite element numerical modelling software (HYDRUS 2-D) to estimate the range of recharge rates for the study area. Based on field infiltration test results, the hydraulic conductivity was found to be 0.3 19.9 cm/hr; typical for silty sands to fine sands. Hydraulic conductivities estimated in the laboratory were greater than the field hydraulic conductivity by 103%. This could be attributed to entrapped air under field conditions which reduces the effective cross-sectional area available for water to flow. From the HYDRUS 2-D simulations, the period required for the wetting front movement from the pond surfaces to the water table ( 5.5 m below the surface) was 15 140 hours. Hydraulic conductivities estimated using the pedotransfer function (PTF) of the built-in software, Rosetta-Lite, were also greater than the field hydraulic conductivity values by 118%. For an actual test pond, the infiltration rates would be expected to be slower, and recharge times would be greater because the HYDRUS 2-D simulations did not consider layers of low permeability suggestion that the field saturated hydraulic conductivity could be taken as roughly 0.5 times the laboratory hydraulic conductivity was thus considered reasonable. This means that ponds in the central area of the catchment would be suitable for artificial recharge with an estimated infiltration rate of around 20.6 cm/hr which could provide a mean annual groundwater yield of 29 33 Mm3 . A more extensive survey would aid in assessing local conditions that may impede groundwater flow.